Reviews of Physiology, Biochemistry and Pharmacology, Vol. 164 - Nilius, Bernd; Amara, Susan G.; Lill, Roland; Offermanns, Stefan; Gudermann, Thomas; Petersen, Ole H.; Jahn, Reinhard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
T. Hara, I. Kimura, D. Inoue, A. Ichimura, and A. Hirasawa: Free fatty acid receptors and their role in regulation of energy metabolism. B. Nilius and G. Appendino. Spices: the savory and healthy science of pungency.
Keywords: Medicine; Human physiology; Gastroenterology; Metabolic diseases; Biomedicine; Human Physiology; Metabolic Diseases; Gastroenterology